2008
DOI: 10.1056/nejmoa0708191
|View full text |Cite
|
Sign up to set email alerts
|

Bivalirudin during Primary PCI in Acute Myocardial Infarction

Abstract: ResultsAnticoagulation with bivalirudin alone, as compared with heparin plus glycoprotein IIb/IIIa inhibitors, resulted in a reduced 30-day rate of net adverse clinical events (9.2% vs. 12.1%; relative risk, 0.76; 95% confidence interval [CI] 0.63 to 0.92; P = 0.005), owing to a lower rate of major bleeding (4.9% vs. 8.3%; relative risk, 0.60; 95% CI, 0.46 to 0.77; P<0.001). There was an increased risk of acute stent thrombosis within 24 hours in the bivalirudin group, but no significant increase was present b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

44
1,191
19
33

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 1,711 publications
(1,287 citation statements)
references
References 29 publications
44
1,191
19
33
Order By: Relevance
“…The ACUITY and HORIZONS AMI trials were excluded because these open label trials included a bivalirudin-based strategy. 42,43 Lastly, several trials used a higher dose of unfractionated heparin in the control arm than the GPI arm. This difference might have diminished the relative efficacy of GPIs and masked any increased tendency toward bleeding.…”
Section: Limitationsmentioning
confidence: 99%
“…The ACUITY and HORIZONS AMI trials were excluded because these open label trials included a bivalirudin-based strategy. 42,43 Lastly, several trials used a higher dose of unfractionated heparin in the control arm than the GPI arm. This difference might have diminished the relative efficacy of GPIs and masked any increased tendency toward bleeding.…”
Section: Limitationsmentioning
confidence: 99%
“…The recently published UK HEAT-PPCI trial showed that heparin led to a lower incidence of ischemic events and a similar incidence of bleeding compared with bivalirudin, suggesting that heparin might be a more costeffective treatment on the basis of these results and its lower cost. 37 In addition to a significant reaction to its delayed consent strategy, the trial has generated much debate in the medical community because of the difference in results compared with previous trials of bivalirudin versus heparin, [38][39][40] although interestingly, a subsequent US study 41 also yielded similar results. It is not clear whether the current debate will influence the next update to the STEMI guidelines, although it is important for all health care professionals treating cardiology patients to be aware of the potential implications with respect to clinical practice as the discussions and investigations will no doubt continue.…”
Section: In Stemi Patients Who Are Receiving Antiplatelet Agents and mentioning
confidence: 99%
“…To attenuate the risk of future thrombotic events, patients with ACS are treated with dual antiplatelet therapy (DAPT), namely, the combination of aspirin with a P2Y 12 inhibitor, such as clopidogrel, ticagrelor, or prasugrel. Despite DAPT, some ≈10% of ACS patients experience recurrent major adverse cardiovascular events over the subsequent 30 days,2 driving the quest for more effective inhibition of thrombotic pathways. In this review, we provide an overview of studies to date and those ongoing that aim to deliver more effective combinations of antithrombotic agents to patients with recent ACS.…”
Section: Introductionmentioning
confidence: 99%